Measurements of the quality of nematic liquid crystal alignment - Ostromęcka, Iga; Kwaśny, Michał; Jung, Paweł; Klus, Bartłomiej Wojciech; Laudyn, Urszula Anna (Photonics Letters of Poland, 2016)
In this paper we have investigated the alignment of nematic liquid crystal (NLC) molecules in homogenously oriented liquid crystal cells used for nematicons generation. We propose three different methods based on contrast evaluation, linear diffraction and nematicons generation. We showed that LC cell contrast evaluation is not enough from the perspective of nematicons generation. In order to select the best LC cell all of proposed methods should be combined with each other. Full Text: PDF References S. Trillo, W. Torruellas, Spatial Solitons (Springer, Berlin 2001). G. Assanto, Nematicons (Wiley, 2012). CrossRef M. Peccianti, G. Assanto, "Nematicons", Phys. Rep. 516, 147 (2012). CrossRef Ya.V. Izdebskaya, J. Rebling, A.S. Desyatnikov, G. Assanto, Yu.S. Kivshar, "All-optical switching of a signal by a pair of interacting nematicons", Opt. Express 20, 24701 (2012). CrossRef A. Piccardi, et al., "Trends and trade-offs in nematicon propagation", Appl. Phys B 104, 5 (2011). CrossRef S.V. Serak, N.V. Tabiryan, M. Peccianti, G. Assanto, "Spatial soliton all-optical logic gates", IEEE Phot. Tech. Letters 18(12), 1287 (2006). CrossRef A. Piccardi, U. Bortolozzo, S. Residori, and G. Assanto, "Spatial solitons in liquid-crystal light valves", Opt. Lett. 34, 6 (2009). CrossRef U.A. Laudyn, M. Kwasny, M.A. Karpierz, "Electric-field-induced steering in soliton direction of propagation in chiral nematic liquid crystals", Opt. Comm. 283, 1463 (2010). CrossRef U.A. Laudyn, M.A. Karpierz, "Nematicons deflection through interaction with disclination lines in chiral nematic liquid crystals", Appl. Phys. Lett. 103, 221104 (2013). CrossRef P. Yeh, C. Gu, Optics of Liquid Crystal Displays (Wiley, 1999). I.C. Khoo, Liquid Crystals (Wiley, 2007). Q. Li, Nanoscience with Liquid Crystals (Springer, 2014). CrossRef L. Vretik, O. Yaroshchuk, V. Zagnii, V. Kyrychenko, V. Syromyatnikov, Liquid crystalline organic compounds and polymers as materials of XXI century: From synthesis to applications, A. Iwan and E. Schab-Balcerzak (Ed.), Transworld Research Network, Chapt. 6, pp.153-189 (2011). C. Conti, M. Peccianti, G. Assanto, "Observation of Optical Spatial Solitons in a Highly Nonlocal Medium", Phys. Rev. Lett. 92, 113902 (2004). CrossRef